An overview of quantitative approach in welfare service delivery research - Samihah Khalil @ Halim,; Salihu, Abdulwaheed Adelabu (Sunway University, 2012)
Quantitative research stresses on an inquiry that attempts to systematically measure and predict phenomena through the use of standardized tools. The paper aims to demonstrate the utilization of systematic procedures of conducting quantitative research on the delivery of primary education and healthcare service by local governments. Specifically, this paper describes research design, sampling framework, instrumentation, measurement of variables, reliability and validity, piloting the questionnaire and redesigning the final instrument. The Modified Quantitative Service Delivery Survey (MQSDS) constructed for the study is an effective tool to be used in determining the status of service delivery by local governments in Nigeria